Quality of Life for Hemodialysis Patients in Kirkuk Governorate / Iraq - Rebaz Ismail Ali Al–Brzanji; Rifaie Yaseen Hameed (Kufa Journal for Nursing Sciences)
Objectives: to assess Quality of Life (QoL) for dialysis patients and to predict the correlations among the domains of quality of life.